Comparative proteomic analysis reveals the pathological mechanisms of overuse achilles tendinopathy and the therapeutic mechanisms of ESWT and PRP - Gongzi Zhang; Tianshu Zhao; Yangxiaoxue Liu; Jianing Xu; Wenxi Luo; Hao Liu; Bei Liu; Jingxian Hou; Jiali Zhang; Ruining Wu; Ming Zhou; Liping Huang (Tissue and Cell, 2026)

Enhanced water level fluctuations reduced the competitive advantage of cyanobacteria - Yan Chen; Rui Xia; Ruining Jia; Junde Ming; Kai Zhang; Jinghui Dou; Tianxiang Zhao; Xiang Li; Qin Zhang; Qi Zhang (Journal of Hydrology, 2026)

An experimental and kinetic modeling study of the autoignition delay times of triethyl phosphite - Frederick Nii Ofei Bruce; Yuke Gao; Ruining He; Zhihan Zhu; Xin Wang; Yilin Zhao; Mengmeng Jia; Jiaxin Xie; Xin Bai; Yun Hin Taufiq-Yap; Chong-wen Zhou; Henry Curran; et al. (Fuel, 2026)

An exploration into the transplacental transfer of microplastics through placental transporters - Binbin Guo; Yawei Wang; Weilin Wang; Ruining Guan; Dongquan Li; Qiyue Wang; Chunyan Zhao (Journal of Environmental Sciences, 2026)

An experimental study on the ignition and combustion characteristics of ultrafine boron particles - Ruining He; Xin Bai; Xuan Ren; Yilin Zhao; Xin Wang; Jinhu Liang; Fei Qin; Ce Sun; Taufiq Yap Yun Hin; Chong-Wen Zhou; Henry J Curran; Yang Li (Fuel, 2026)

Liquid phase transformation mechanism of amphetamine initiated by •OH, HO2•, and 1O2 in advanced oxidation processes - Ruining Han; Peiwen Hu; Yan Wang; Chongwen Sun; Xuemin Zhao; Xiaomin Sun (Journal of Environmental Chemical Engineering, 2026)

Bifunctional modulation of MrBBX19 on repressor MrNAC47 and activator MrMYB12 for UV-B-mediated quercetin enhancement in Chinese bayberry (Morella rubra) - Ruining Zhang; Qianyu Wang; Jiajia Li; Jiafei Qian; Xiangrui Cui; Yunlin Cao; Yilong Liu; Xiaoyong Zhao; Di Wu; Changjie Xu; Kunsong Chen; Xian Li (Food Chemistry, 2026)

Effects of high hydrostatic pressure on starch: multi-scale structures, interactions and applications - Yuqian Zheng; Xiaoyan Qin; Wenyan Wang; Zhilong Chen; Wenlong Xie; Jun Zhao; Ruining Zhang; Sheng Li (Food Chemistry, 2025)

Ultrasensitive and rapid electrochemical detection of nitrite based on gold nanoparticles-poly(phenylboronic acid) modified electrode and I2/I− probe - Xuedong Jia; Hongyuan Guo; Xiu Zhao; Ruining Liu; Xiayu Song; Zhuo Shi; Yingchun Zhu; Suozhu Wu (Food Chemistry, 2025)

Exploring the toxicological network of bleomycin-induced pulmonary fibrosis: The role of long non-coding RNAs - Bingxin Li; Hongbin Shi; Yun Ma; Ruining Zhao; Haijun Zhang (Food and Chemical Toxicology, 2025)

β-galactanase: an effective tool for the degradation of plant β-ᴅ-galactan - Yanbo Hu; Yuzhu Shen; Yudi Song; Yue Yang; Yakun Shan; Ruining Zhang; Jun Zhao (World Journal of Microbiology and Biotechnology, 2025)

Polystyrene and polyethylene perturb the structure of membrane: An experimental and computational study - Ruining Guan; Qiyue Wang; Dongquan Li; Binbin Guo; Weilin Wang; Ningqi Li; Jinlong Zhang; Ruitong Cai; Zeyang Cui; Haixia Zhang; Chunyan Zhao (Environmental Pollution, 2025)

Phytochemical investigation of Jie-Geng-Tang and regulatory role in the TNF-α pathway in mitigating pulmonary fibrosis using UPLC-Q-TOF/MS - Bingxin Li; Ruining Zhao; Xiaojie Jiang; Chang Liu; Yun Ma; Haijun Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A Large-Scale Focused Fluid Flow Zone Between Atolls in the Xisha Islands (South China Sea): Types, Characteristics, and Evolution - Jixiang Zhao; Benjun Ma; Zhiliang Qin; Wenjian Lan; Benyu Zhu; Shuyi Pang; Mingzhe Li; Ruining Wang (Journal of Marine Science and Engineering, 2025)
A large number of seabed depressions, covering an area of 2500 km2 in the Xisha Massif of the South China Sea, are investigated using newly collected high-resolution acoustic data. By analyzing the morphological features and seismic attributes of the focused fluid flow system, five geological structures are recognized and described in detail, including pockmarks, volcanic mounds, pipes, faults, and forced folds. Pockmarks and volcanic mounds occur as clustered groups and their distributions are related to two large-scale volcanic zones with chaotic seismic reflections. Pipes, characterized by disordered seismic reflections, mainly occur within the focused fluid flow zone (FFFZ) and directly link with the large-scale deep volcano and its surrounding areas. Faults and fractures mainly occur along pipes and extend to the seafloor, commonly presenting lateral walls of mega-pockmarks. Forced folds are primarily clustered above volcanic zones and commonly restricted between faults or pipes, characterized by sediment deformations as indicated in seismic profiles. By comprehensive analysis of the above observations and a simplified simulation model, the volcanism-induced hydrothermal fluid activities are argued herein to contribute to these focused fluid flow structures. In addition, traces of suspected submarine instability disasters such as landslides have been found in this sea area, and more observational data will be needed to determine whether seafloor fluid flow zones can be used as a predictor of seafloor instability in the future.

Toxicity assessment and i-QSTTR analysis of ionic liquids on D. magna, D. rerio, and R. subcapitata - Ruining Guan; Ningqi Li; Ruitong Cai; Binbin Guo; Qiyue Wang; Dongquan Li; Chunyan Zhao (Science of The Total Environment, 2025)

Exploring the preventive effects of Jie Geng Tang on pulmonary fibrosis induced in vitro and in vivo: a network pharmacology approach - Bingxin Li; Xiaojie Jiang; Chang Liu; Yun Ma; Ruining Zhao; Haijun Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Intertwined role of mechanism identification by DFT-XAFS and engineering considerations in the evolution of P adsorbents - Ruining Zhao; Benhang Li; Siyuan Chen; Boxuan Zhang; Jiale Chen; Jiahe Sun; Xiaodong Ma (Science of The Total Environment, 2024)

Natural mineral and industrial solid waste-based adsorbent for perfluorooctanoic acid and perfluorooctane sulfonate removal from surface water: Advances and prospects - Siyuan Chen; Benhang Li; Ruining Zhao; Boxuan Zhang; Yuqing Zhang; Jiale Chen; Jiahe Sun; Xiaodong Ma (Chemosphere, 2024)

Overexpression of MrMYB12 or MrMYB12/MrF3’5’H results in flavonol-rich tomato fruit that improves resistance against Botrytis cinerea during the shelf life period - Yunlin Cao; Ruining Zhang; Ruohan Ou; Yuyang Mei; Xiangrui Cui; Tong Zhang; Xiaochun Yang; Yanna Shi; Xiaoyong Zhao; Changjie Xu; Kunsong Chen; Xian Li (Postharvest Biology and Technology, 2024)

A critical review on the bioaccumulation, transportation, and elimination of per- and polyfluoroalkyl substances in human beings - Yao Lu; Ruining Guan; Nali Zhu; Jinghua Hao; Hanyong Peng; Anen He; Chunyan Zhao; Yawei Wang; Guibin Jiang (Critical Reviews in Environmental Science and Technology, 2024)

Efficient low-concentration phosphate removal from sub-healthy surface water by adsorbent prepared based on functional complementary strategy - Benhang Li; Yanhao Chen; Gengbo Ren; Ruining Zhao; Zhineng Wu; Fujie Zhu; Xiaodong Ma (Science of The Total Environment, 2023)

Machine learning models based on residue interaction network for ABCG2 transportable compounds recognition - Ruining Guan; Wencheng Liu; Ningqi Li; Zeyang Cui; Ruitong Cai; Yawei Wang; Chunyan Zhao (Environmental Pollution, 2023)

Magnetic biochar-based manganese oxide composite for enhanced fluoroquinolone antibiotic removal from water - Ruining Li; Zhaowei Wang; Xiating Zhao; Xi Li; Xiaoyun Xie (Environmental Science and Pollution Research, 2018)

Molecular Cloning and Identification of the 2′–5′ Oligoadenylate Synthetase 2 Gene in Chinese Domestic Pigs Through Bioinformatics Analysis, and Determination of Its Antiviral Activity Against Porcine Reproductive and Respiratory Syndrome Virus Infection - Ruining Wang; Hongfang Ma; Yinfeng Kang; Cunfa Li; Huawei Li; Erqin Zhang; Pengchao Ji; Jian He; Mengmeng Zhao (Indian Journal of Microbiology, 2018)